The impact of nutritional therapy in malnourished patient with tongue squamous cell carcinoma undergoing chemoradiation - Debtia Rahmah; Diana Sunardi; Nurul Ratna Mutu Manikam (World Nutrition Journal, 2026)
Background: Malnutrition affects 30%-50% of patients with head and neck carcinoma. It is associated with reduced survival, increased risk of complications, treatment interruption, and higher treatment-related toxicity.1,2 Objective: This case aim to discuss about nutritional therapy in tongue carcinoma patient with malnourished and cachexia undergoing chemoradiotherapy. Case: A 52-year-old man with squamous cell carcinoma of the tongue presented with clinically severe malnutrition and cachexia. Imaging revealed a solid mass involving the entire tongue and extending to the floor of the mouth, resulting in dysphagia. He undergo locoregional Intensity-Modulated Radiation Therapy (IMRT) 70/56 Gy in 35 fractions in concomitant with chemotherapy. Nutritional management involves enteral feeding with a gradual increase in energy intake from 40 kcal/kg body weight (BW) to 63 kcal/kg BW and protein from 2 to 3 g/kg BW. The patient received daily micronutrient supplementation consisting of 1 tablet of vitamin B complex three times daily, vitamin C 50 mg twice daily, zinc 20 mg twice daily, folic acid 500 mcg once daily. He also given 1 gram eicosapentaenoic acid (EPA). After one month, the patient demonstrated a weight gain of 1.8 kg (4.3%), increased handgrip strength, and functional capacity. Body composition analysis demonstrated increase in fat-free mass index (FFMI) from 15.2 to 15.8 kg/m2, skeletal muscle index (SMI) from 5.6% to 5.9%, and fat mass from 5.3% to 5.6%. Conclusion: Adequate energy and high protein intake along with micronutrients and EPA supplementation may help prevent deterioration of nutritional status, increase body weight, preserve muscle mass, and improve functional capacity in cancer patient undergoing chemoradiotherapy.